The Synergistic Effect of Leukocyte Platelet-Rich Fibrin and Micrometer/Nanometer Surface Texturing on Bone Healing around Immediately Placed Implants: An Experimental Study in Dogs. (30th November 2016) - Neiva, Rodrigo F.; Gil, Luiz Fernando; Tovar, Nick; Janal, Malvin N.; Marao, Heloisa Fonseca; Bonfante, Estevam Augusto; Pinto, Nelson; Coelho, Paulo G.
Abstract : Aims . This study evaluated the effects of L-PRF presence and implant surface texture on bone healing around immediately placed implants. Methods . The first mandibular molars of 8 beagle dogs were bilaterally extracted, and implants (Blossom™, Intra-Lock International, Boca Raton, FL) were placed in the mesial or distal extraction sockets in an interpolated fashion per animal. Two implant surfaces were distributed per sockets: (1) dual acid-etched (DAE, micrometer scale textured) and (2) micrometer/nanometer scale textured (Ossean™ surface). L-PRF (Intraspin system, Intra-Lock International) was placed in a split-mouth design to fill the macrogap between implant and socket walls on one side of the mandible. The contralateral side received implants without L-PRF. A mixed-model ANOVA (at α = 0.05 ) evaluated the effect of implant surface, presence of L-PRF, and socket position (mesial or distal), individually or in combination on bone area fraction occupancy (BAFO). Results . BAFO values were significantly higher for the Ossean relative to the DAE surface on the larger mesial socket. The presence of L-PRF resulted in higher BAFO. The Ossean surface and L-PRF presence resulted in significantly higher BAFO. Conclusion. L-PRF and the micro-/nanometer scale textured surface resulted in increased bone formation around immediately placed implants.